Differential ER stress as a driver of cell fate following ricin toxin exposure. Issue 1 (19th October 2021) - Peterson‐Reynolds, Claire; Mantis, Nicholas J.
Abstract: Inhalation of trace amounts of ricin toxin, a plant‐derived ribosome‐inactivating protein, results in ablation of alveolar macrophages, widespread epithelial damage, and the onset of acute respiratory distress syndrome (ARDS). While ricin's receptors are ubiquitous, certain cell types are more sensitive to ricin‐induced cell death than others for reasons that remain unclear. For example, we demonstrate in side‐by‐side studies that macrophage‐like differentiated THP‐1 (dTHP‐1) cells are hyper‐sensitive to ricin, while lung epithelium‐derived A549 cells are relatively insensitive, even though both cell types experience similar degrees of translational inhibition and p38 MAPK activation in response to ricin. Using a variety of small molecule inhibitors, we provide evidence that ER stress contributes to ricin‐mediated cytotoxicity of dTHP‐1 cells, but not A549 cells. On the other hand, the insensitivity of A549 cells to ricin was overcome by the addition of (TNF)‐related apoptosis‐inducing ligand (TRAIL; CD253), a known stimulator of extrinsic programmed cell death. These results have implications for understanding the complex pathophysiology of ricin‐induced ARDS in that they demonstrate that intrinsic (e.g., ER stress) and extrinsic (e.g., TRAIL) factors may ultimately determine the fate of specific cell types following ricin intoxication.